PENGOMPOSAN SEKAM PADI MENGGUNAKAN SLURRY DARI FERMENTASI LIMBAH CAIR PABRIK KELAPA SAWIT - Irvan, Bambang Trisakti, Cut Novaliani Hasbi, Elwina Widiarti (Universitas Sumatera Utara, 2013)
Rice husk is material waste that is usually just burned. However, this practice is causing air pollution problems. One effort to help overcome the problem of agricultural waste is recycling technique with an emphasis on the process of composting. Many efforts can be made ​​to speed the composting process. The treatment was performed by the addition of slurry at the beginning of composting process with the addition of as much as 1, 2,and 3 liters and the addition of slurry during composting process by adding 0,5;1; and 1,5liters of slurry every 3 days once. At each treatment was added 1 kg of fine compost. The condition which almost meets quality compost by SNI 19-7030-2004 and most precocious and decomposesis the compost with the addition of as much as 1, 5 liters every 3 days where the temperature is 32,8 oC obtained, the water level is 35,1,99 %, the ratio of C / N is 7.58 and pH is 9,59. This thing indicates that the slurry from biogas fermentor can accelerate the maturity of compost making so that it is more easily broken down or decomposed.